Tinjauan Sistematis: Keefektifan Model Pembelajaran Kooperatif Tipe STAD Berbantuan Simulasi Phet Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Menengah Pada Mata Pelajaran Fisika - Alia Cahyani (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2024)
This study aims to systematically analyze the effectiveness of the cooperative learning model Student Teams Achievement Division (STAD) assisted by PhET simulations in improving secondary school students’ critical thinking skills in physics. The research employed a Systematic Literature Review (SLR) referring to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data sources were obtained from documents indexed in Google Scholar within the 2014–2024 range and were analyzed bibliometrically using VOSviewer software. A total of 18 relevant articles were examined to identify trends, effectiveness, and the influence of the learning model on students’ critical thinking skills. The review findings reveal that the integration of the STAD model with PhET simulations is effective in enhancing critical thinking abilities, conceptual understanding, and students’ learning motivation. These results are supported by a systematic review conducted by Baqy, Damayanti, & Rokhmat (2025), which indicates that cooperative learning models such as STAD, Jigsaw, TPS, and TSTS consistently improve learning outcomes and critical thinking skills in science education. Thus, collaboration-based learning supported by interactive simulation media such as PhET has strong potential to serve as an effective, contextual, and relevant physics learning strategy aligned with 21st-century educational demands.